ONLINE LEARNING ON ACADEMIC WRITING: IMPLEMENTING THE AUTHENTIC LEARNING APPROACH - Pribadi, Benny Agus; Gafur, Abd (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
Academic writing skills are essential competencies for students to support academic success and scholarly publication; however, many students still struggle to produce publishable academic writing. This study aims to explore the use of an authentic learning approach as a strategy to help students complete academic writing assignments effectively. This study employs a descriptive-analytical approach, using systematic observation of variables. Thirty students who enrolled in the academic writing course of Universitas Terbuka (UT) were involved as respondents in this present study. The participants had to follow the systematic online learning sessions of the academic writing course. After completing the academic writing course, participants must be able to write a proper academic article for a related journal. The academic writing online course was designed and developed with the following nine principles of authentic learning: authentic context, authentic tasks and activities, access to expert performances, multiple roles and perspectives, supporting collaborative construction of knowledge, promoting reflection and articulation, providing coaching and scaffolding, and assessing the students' writing assignment. The results of the study indicated that students' scores increased after completing the authentic learning-based academic writing courses. The study recommends that an authentic learning approach is essential in an academic writing course, as it provides real learning experiences that help students complete the academic writing assignments.